Exploring the role of ethical issues in the context of digital transformation - Angelina Roša (Trends Economics and Management, 2021)
Purpose of the article: The article aims to explore the role of ethics within the context of digital technologies to provide additional insight into the phenomenon of digital transformation, and thus to contribute to a better understanding of the opportunities and challenges that companies encounter in a rapidly changing business environment. Specifically, the paper determines the role of ethics discussed in the most recent scientific literature in the context of digital transformation. Methodology/methods: An explorative approach to the analysis of scientific literature was adopted to answer the research question: What is known from the available scientific literature about the role of business ethics in the digital transformation of a company? The Scopus and ScienceDirect scientific databases were used for the literature search. The selected articles were assessed, grouped around the topics and analysed. Scientific aim: To investigate the challenges in the business ethics related to an increased impact of digital transformation on the company's performance. Findings: 1) Business ethics ensures that digital technologies and the company's decisions based on the information provided by these technologies are in line with the ethical considerations. 2) There is a demand for the increased organisational accountability for data management to ensure legal and ethical implications of data ownership. 3) Ethical decisions promote a longrun sustainable development of a company. 4) Ethical decision-making allows digitalisation solutions to be applied in accordance with the values and principles of employees. Conclusions: Ethical considerations provide deeper understanding of the impact of digital transformation at a higher level and in its long-term perspective. Limitations: the literature search was conducted in two scientific databases. Implications: the findings of this study form the basis for further research to investigate the interdependence between ethical responsibility of a company and technological advances towards achieving sustainable development.
Keywords: M15; M21; 650; digital transformation; business ethics; ethical values; ethical behaviour; business environment; sustainable performance